An innovative design education approach:: Computational design teaching for architecture - Colakoglu, Birguel; Yazar, Tugrul (MIDDLE EAST TECHNICAL UNIV, 2007)
This paper describes an innovative design education approach developed to explore new intellectual and theoretical directions of design generation. It utilizes algorithms as a tool for introducing the concept of design computing to graduate students of architecture. The graduate course titled Designing the Design is thus developed. The aim of the course is to introduce to the students of architecture the computational design thinking and the new emerging language and method of designing. Examples from the course process are given to illustrate explorations in this new auxiliary teaching method of the design.
Keywords: computational design thinking; computational design; algorithmic thinking; computational design education; Architecture